2017
DOI: 10.2989/1814232x.2017.1363817
|View full text |Cite
|
Sign up to set email alerts
|

Use of otolith-shape analysis for stock discrimination of Boops boops along the Algerian coast (southwestern Mediterranean Sea)

Abstract: Otolith-shape analysis was examined to determine its utility for biological stock identification of the bogue Boops boops along the Algerian coast of the Mediterranean Sea. The outlines of 179 sagittal otolith pairs from fish collected at three locations (Oran, Bejaia and Annaba) between 2013 and 2016 were digitised and analysed for shape variation by elliptical Fourier analysis. Potential confounding sources of variation (fish length, age and sex, and left or right otolith position) were examined and accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(65 reference statements)
3
17
0
Order By: Relevance
“…Elliptic Fourier analysis of the otolith contour shape revealed a clear asymmetry between the left and right sides within and between the fish samples in the two localities. These results are consistent with those previously cited on the sparid Oblada melanura (Linnaeus, 1758) (see Barhoumi et al 2018), Diplodus annularis (see Trojette et al 2015), and Pagellus erythrinus (see Mejri et al 2018Mejri et al , 2020, which are cohabiting different habitats in Tunisian waters, as well as on the B. boops sampled from three locations along the Algerian coast (Ider et al 2017) and from the Gulf of Tunis (Mahé et al 2019). Similarly, the asymmetry of the otolith shape has also been found in other species that live elsewhere outside of Tunisian waters, such as Gadus morhua Linnaeus, 1758 (see Campana andCasselman 1993, Hüssy et al 2016) Khemiri et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Elliptic Fourier analysis of the otolith contour shape revealed a clear asymmetry between the left and right sides within and between the fish samples in the two localities. These results are consistent with those previously cited on the sparid Oblada melanura (Linnaeus, 1758) (see Barhoumi et al 2018), Diplodus annularis (see Trojette et al 2015), and Pagellus erythrinus (see Mejri et al 2018Mejri et al , 2020, which are cohabiting different habitats in Tunisian waters, as well as on the B. boops sampled from three locations along the Algerian coast (Ider et al 2017) and from the Gulf of Tunis (Mahé et al 2019). Similarly, the asymmetry of the otolith shape has also been found in other species that live elsewhere outside of Tunisian waters, such as Gadus morhua Linnaeus, 1758 (see Campana andCasselman 1993, Hüssy et al 2016) Khemiri et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this species is demersal, as well as semi-pelagic, gregarious, and lives on all types of the bottom substrata, including mud, rock, sand, and seagrass beds (Simsek et al 2018). However, it is commonly found at depths between 50 and 350 m and in coastal waters, it sometimes moves in aggregations, ascending mainly to the surface at night (Ider et al 2017). Pollard et al (2014) mentioned that B. boops grows rapidly in length during the first year of life, where it reaches 53.49% of its final length of growth and can live up to seven years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stock structure is similar to that observed for other species in the same areas such as sardine or cephalopods (see Jemaa et al, 2015;Keller et al, 2017). Ider et al (2017) analyzing only the data from the Algerian coasts, identified only one stock for this area just as the present study conducted at much larger geographic scale, which indicates consistency of otolith shape-based stock discrimination across multiple geographic scales. Factors structuring bogue stocks at the level of the Mediterranean region seem to be linked to environmental features, notably physical oceanographic characteristics of the studied area.…”
Section: Stock Structure Of Bogue In the Mediterranean Sea And The Atsupporting
confidence: 47%
“…In addition, this is a demersal species, as well as semi-pelagic, gregarious, and lives on all types of the bottom substrata, including mud, rock, sand and seagrass beds (Ceyhan et al, 2018;Şimşek et al, 2018). It is commonly found at depths between 50-350 m and in coastal waters, it sometimes moves in aggregations, ascending mainly to the surface at night (Rachid et al, 2014;Ider et al, 2017). Pollard et al (2014) reported that B. boops grows rapidly in length during the first year of life, where it reaches 53.49% of its final growth length and can live up to 7 years.…”
Section: Introductionmentioning
confidence: 99%